Microsoft solutions framework (MSF) as a generalized methodology of the framework appoach to spatial information systems handling - Chabaniuk, V.; Dyshlyk, O. (Land Management, Cadastre and Land Monitoring, 2025)
In the article “Framework approach as a strategy for research and design of complex spatial information systems (using the example of NGDI)” the names of its three possible interpretations are formulated. The first of them – as a specific constructive strategy for using geographic information systems and technologies (GIS&T) to manage the territory of Ukraine - considered there also. This paper explores the second interpretation of the Framework Approach – as a generalization of the methodology for SpIS handling. The notion of “generalized methodology” is at the same “epistemological” level of the hierarchy of notions as the notion of “constructive strategy”. To consider this correspondence, the notion of “meta X” is used, where X takes the values necessary for this work. From a theoretical viewpoint, the main attention paid to the notion of “meta-research” and its component - the notion of “meta-methodology”. From a practical viewpoint, the main attention paid to the notions “methodology” and “meta-methodology”, known since the end of the last century as the Microsoft Solutions Framework (MSF, versions 1.0 – 4.0). Moreover, such understandings of “generalized methodology” selected that correspond to the notion of “meta-methodology” in the context of the Framework Approach to SpIS handling. Paying due respect to the origin of the term “Solutions Framework (SoFr)”, the consideration of the generalized methodology (or generalization of methodologies) begins with a reminder of version 2.0 of the MSF methodology, to all versions of which the abbreviation M SoFr (Microsoft SoFr) is applied. Such a notation makes it logical to ask about the similarities between M SoFr and the previously considered X(Y) SoFr, such as GeoSF (GeoSolutions Framework) or AtlasSF (Atlas Solutions Framework). Some of these similarities discussed in the article. At the turn of the century, the MSF 2.0 methodology consisted of six Microsoft models (solutions), some of which we used in practice: 1) enterprise architecture, 2) project team, 3) risk management, 4) application development process, 5) design process, 6) enterprise application. All of them described in the MCSD70-100 exam using the example of a hypothetical application that was relevant at that time. Then the MSF 2.0 methodology generalized, so that MSF version 4.0 included two methodologies: MSF for Agile Software Development (MSF4ASD) and MSF for CMMI Process Improvement (MSF4CMMI). There are sources in which the mentioned constructs called approaches. The following relations are valid: 1) MSF4ASD ↑ MSF 4.0, 2) MSF 4.0 ↓ MSF4CMMI. The relation ↑ is epistemological, and the relation ↓ is reductive. The ↑↓ relations are supplemented by inclusion relations: MSF 4.0 = MSF4ASD ∪ MSF4CMMI. Updating MSF 4.0 and presenting it with a modern generalization of the methodology for SpIS handling is necessary for the possible reduction from it of currently practically useful methodologies. In particular, built using modern Microsoft products, open source products, including our “extension methodology”, as well as others. Formally, the MSF notion is not currently being developed and the methodological constructs of MSF are hypothetical, however, the phenomenon of MSF itself actually exists, is developing and is used. The actual now MSF version in this article is interpreted as a meta-methodology, from which, by reduction (specification or specialization), it is possible to obtain the methodology for SpIS handling, necessary for practice and including actual Microsoft information technologies. The renewal of our interest to Microsoft solutions and technologies explained not only by their usefulness, but also by the more than ten-year strategy of their gradual openning by the parent (author) company. Due to this fact, by reduction (one or two) from the MSF meta-methodology, we expect to obtain our “extension methodology”. The more traditional name of the latter is Pattern-Based Spatial Engineering (PBSE) due to the fact that it is now being created as Model-Based Software Engineering. The latter will be Model-Based Systems Engineering. Keywords: generalized methodology for SpIS handling, MSF methodology and meta-methodology, Pattern-Based Spatial Engineering (PBSE).